Two Literary Universities on the Borders of the Mexican Nation. Mérida/Yucatan and San Cristóbal de las Casas/Chiapas, 1812-1855: Deux universités littéraires dans les limites de la nation mexicaine Mérida/Yucatán et San Cristóbal de las Casas/Chiapas, 1812-1855 - Rosas Iñiguez, Cristian M. (Historia y Memoria de la Educación, 2024)
This article seeks out two Mexican universities which were founded after the First Federal Republic was declared in 1824. Those institutions had been put aside for traditional historiography of colleges and universities, even they were located in two important states in south Mexico: one in San Cristobal Las Casas, Chiapas, and the other in Merida, Yucatán. They joined the other two universities already functioning in the country, one in Mexico City and the other in Guadalajara, and received the adjective “literarias”. The analysis looks at different aspects of those universities such as administration, academics and including some points of financing. Also, it shows the context in which these universities functioned, because it helps to understand how they developed. The aim is to demonstrate the value that these two universities had in the construction of each state where they were situated and try to answer about their integration or not in the emergent educational system. At the end, this article seeks to give an explanation of the complex condition of these universities into the heterogeneous situation of colleges and universities in the first part of Nineteenth Century Mexico.